2014
DOI: 10.1186/1745-6673-9-19
|View full text |Cite
|
Sign up to set email alerts
|

Nautical officers at sea: emergency experience and need for medical training

Abstract: BackgroundOn merchant ships, the medical treatment including emergency interventions on the high seas are carried out by nautical officers who have to pass a forty hours medical refresher course every five years in order to meet international requirements. This study aims to show the most frequent kinds of medical emergencies on the high seas and to assess the seafarers’ knowledge about their treatment.Methods465 nautical officers who participated in the medical refresher course at the Institute for Occupation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…In a recent German survey, 465 nautical officers who participated in the medical refresher course at the Institute for Occupational and Maritime Medicine in Hamburg were interviewed about their experience of serious diseases and accidents on board, which had led to an emergency port call, a course deviation or an evacuation [9]. 133 (28.6%) seafarers reported on an experience of at least one serious medical emergency at sea during their seafaring time.…”
Section: Prevalence Of Cvd In Seafarersmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent German survey, 465 nautical officers who participated in the medical refresher course at the Institute for Occupational and Maritime Medicine in Hamburg were interviewed about their experience of serious diseases and accidents on board, which had led to an emergency port call, a course deviation or an evacuation [9]. 133 (28.6%) seafarers reported on an experience of at least one serious medical emergency at sea during their seafaring time.…”
Section: Prevalence Of Cvd In Seafarersmentioning
confidence: 99%
“…With regard to the vessel type, a high number of CVD occurred particularly on passenger liners (29.4%) with many and frequently older people on board. Besides passenger liners, the occurrence of serious CVD required a course deviation in 10 out of 69 reported cases on container ships [9].…”
Section: Prevalence Of Cvd In Seafarersmentioning
confidence: 99%
“…It encompasses the occupational health of the employees onboard, infectious diseases, the personal hygiene of seafarers, vaccinations, and other preventive interventions, as well as crew health counselling (Peltz & Warger, 2002). This stream of medicine also includes the training of seafarers in providing first aid and basic medical services onboard during voyages, health standards for work at sea, medical examinations of seafarers, and radio medical advice for ships (Carter, 2011;Oldenburg et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Cardiovascular diseases (CvD) have traditionally been a major concern in commercial maritime operations, mainly due to the potential risk of serious complications such as sudden death. Although cardiovascular cases are not a frequent cause of telemedical advice (11 th cause telemedical advice [1]) they remain the principal cause of medical emergencies, medical evacuations and natural deaths on board [2,3]. It might be assumed that seafarers constitute a healthier population compared to employees ashore (healthy worker effect) since their medical fitness is certified at least biennially.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that recording and transmitting electrocardiogram (ECG) is technically feasible and enables timely initiation of antithrombotic therapy [12]. More intensive training of deck officers remains a fundamental measure against potential cardiovascular emergencies [3], while the applicability of automated external defibrillators remains controversial [1]. The prompt implementation of the pre-employment medical examinations (PEMEs) is the cornerstone of CvD prevention.…”
Section: Introductionmentioning
confidence: 99%